CMET-23. IMPACT OF SYSTEMIC THERAPY IN MELANOMA BRAIN METASTASIS. (11th November 2019) - Sagar, Soumya; Lauko, Adam; Barnett, Addison; (Auston) Wei, Wei; Chao, Samuel; Peereboom, David; Stevens, Glen; Angelov, Lilyana; Yu, Jennifer; Murphy, Erin; Mohammadi, Alireza; Suh, John; et al.
Abstract: BACKGROUND: Melanoma is the third most common malignancy that results in brain metastasis and is associated with a median overall survival (OS) of approximately 9 months. In recent years, management of melanoma brain metastases (MBM) by surgery and radiation [stereotactic radiosurgery (SRS) and whole brain radiation therapy (WBRT)] has been bolstered by targeted therapy and immune checkpoint inhibitors (ICI). METHODS: 351 patients, treated for MBM at our tertiary care center from 2000–2018, were grouped into: received chemotherapy, ICI, or targeted therapy. 34% of patients treated with ICI had received other systemic therapies as well as part of their management. OS was calculated from the date of diagnosis of the brain metastases. The Kaplan Meier analysis was utilized to determine median OS and difference in OS was determined by utilizing the Cox proportional hazard model. RESULTS: The median survival after the diagnosis of brain metastasis was 10.4, 11.96, and 7.06 months in patients who received ICI, chemotherapy and targeted therapy respectively. A multivariate model was developed including the type of systemic therapy, presence of extracranial metastases, age, KPS and number of intracranial lesions. 114 patients underwent SRS alone, 56 underwent SRS and WBRT, 43 underwent SRS and surgical removal, 28 had surgical removal, SRS and WBRT, and 78 had no intracranial therapy. Compared to patients who received chemotherapy, patients who received immunotherapy had a hazard ratio, HR = 0.628 (confidence interval = 0.396 – 0.994, p-value = 0.047). Presence of EC metastases (HR= 1.25, p-value < .001), lower KPS (HR = .97, p-value < .0001) and multiple brain lesions (HR = 1.117, p-value < .0001) were associated with significantly worse OS. CONCLUSIONS: Addition of ICI significantly improves the OS in MBM compared to chemotherapy. Lower performance status, multiple brain metastases, and EC metastases are associated with poor OS.